Tourism Marketing Communication Strategy For West Sumatra in Promoting Tourism Events to Increase Tourist Visits in 2023 - Yudha Pratama putra; Nurul Huda (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: The West Sumatra Provincial Government launched